A Scientific Review of Feature Selection Algorithms and Kernel Methods for SVM Classification Models - Dharmadevi, C; Thaddeus, S (International Journal of Computer Sciences and Engineering, 2024)
Feature selection is crucial for improving the efficiency and effectiveness of machine learning models by identifying and choosing the most pertinent subset of features from the original dataset. This review article comprehensively surveys a diverse range of feature selection techniques in the context of Support Vector Machine (SVM) classification model in machine learning. This research work delves into several prominent techniques, including Mutual Information, Chi-Square, Sequential Feature Selection (SFS), Recursive Feature Elimination (RFE), LASSO, and Random Forest. The study reveals that RFE (Recursive Feature Elimination) emerges as the highly effective feature selection technique, demonstrating superior performance metrics compared to the other methods considered. Additionally, the study proposes the integration of hybrid algorithms to further enhance the performance of SVM classification models. Furthermore, this review extends its scope to encompass an evaluation of various kernel methods within the SVM classification paradigm, offering a comprehensive perspective on their efficacy and performance.